2013
DOI: 10.1165/rcmb.2012-0301oc
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Attenuates Lipopolysaccharide or Oleic Acid-Induced Acute Lung Injury in Mice

Abstract: Leptin is reported to be involved in acute lung injury (ALI). However, the role and underlying mechanisms of leptin in ALI remain unclear. The aim of this study was to determine whether leptin deficiency promoted the development of ALI. LPS or oleic acid (OA) were administered to wild-type and leptin deficient (ob/ob) mice to induce ALI. Leptin level, survival rate, and lung injury were examined. Results showed that leptin levels were predominantly increased in the lung, but also in the heart, liver, kidney, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In this line, leptin’s actions in non-obese, septic patients has earned increased attention (Tzanela et al, 2006; Koch et al, 2010). Leptin administration to non-obese subjects suffering from sepsis syndrome and endotoxemia improves survival, probably by mediating the activity of the immune response (Madiehe et al, 2003; Dong et al, 2013; Landgraf et al, 2014; Siegl et al, 2014; Negrin et al, 2017). Furthermore, exogenous leptin administration to leptin-deficient mice improved the pulmonary bacterial clearance and survival during pneumococcal pneumonia (Hsu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line, leptin’s actions in non-obese, septic patients has earned increased attention (Tzanela et al, 2006; Koch et al, 2010). Leptin administration to non-obese subjects suffering from sepsis syndrome and endotoxemia improves survival, probably by mediating the activity of the immune response (Madiehe et al, 2003; Dong et al, 2013; Landgraf et al, 2014; Siegl et al, 2014; Negrin et al, 2017). Furthermore, exogenous leptin administration to leptin-deficient mice improved the pulmonary bacterial clearance and survival during pneumococcal pneumonia (Hsu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that the administration of leptin induces protection during sepsis syndrome and endotoxemia by reducing the immune response and other deleterious characteristics (Dong et al, 2013; Landgraf et al, 2014; Negrin et al, 2017). Lipopolysaccharide-induced acute lung injury is lessened by exogenous leptin administration (Dong et al, 2013; Landgraf et al, 2014), and hyperleptinemia generates resistance to endotoxemia (Madiehe et al, 2003), improving sepsis survival and modulating the immune response (Siegl et al, 2014). In the same line, decreased plasma leptin enhances susceptibility to mortality induced by endotoxemia (Faggioni et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Leptin-deficient mice (ob/ob) seem to be unaffected [14] or protected [15] from the deleterious effects of endotoxin. On the other hand, Gultekin et al [16] demonstrated that exogenous leptin may be protective role in cerulein-induced acute pancreatitis associated to ALI, and Dong et al [17] showed that leptin-deficient ob/ob mice were more susceptible to LPS-related lethality than lean mice. Therefore, the present study was designed to investigate the effects of acute exogenous leptin treatment in the development of LPS-induced acute lung inflammation in mice.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies where OA is used to form ALI in many species such as rat [25] , mouse [17] , dog [26] and rabbit [27] . Nonenzymatic lipid peroxidation is an important point in the oxidative stress related cellular damage caused by free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods in order to create experimental ALI types have been developed on laboratory animals. The primary ones of these methods are lipopolysaccharide (LPS) [4] , acid aspiration [14] , surfactant consumption with saline lavage [15] , pulmonary ischemia/ reperfusion [16] , cecal ligation and puncturing [5] and application of oleic acid (OA) [17] . OA applied intravascularly cause damage in pulmonary vascular endothelial cells and inflammation in the lungs [6] .…”
Section: Introductionmentioning
confidence: 99%